1995
DOI: 10.1128/jb.177.2.343-356.1995
|View full text |Cite
|
Sign up to set email alerts
|

Caulobacter FliQ and FliR membrane proteins, required for flagellar biogenesis and cell division, belong to a family of virulence factor export proteins

Abstract: Each Caulobacter crescentus cell division generates distinct progeny cells: a stalked cell which is competent for DNA replication, and a motile swarmer cell which initiates DNA replication only after it sheds its flagellum and differentiates into a stalked cell later in the cell cycle. Following the initiation of DNA replication, the flagellar transcriptional hierarchy is activated, culminating in the assembly of a single flagellum at the cell pole opposite that bearing the stalk. The biogenesis of the flagell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
55
0
1

Year Published

1995
1995
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(62 citation statements)
references
References 64 publications
6
55
0
1
Order By: Relevance
“…2d and Fig. 5 (Van Way et al, 1993), fliQp (Zhuang & Shapiro, 1995), flhAp (Ramakrishnan et al, 1991 ;Sanders et al, 1992), fliXp (Mohr et al, 1998) and fliLp (Yu & Shapiro, 1992 that the mcpA promoter is different from other CtrAdependent class II promoters is provided by the finding that transcription of mcpA is inhibited when membrane synthesis is blocked (Brassinga et al, 2000), whilst other flagellar class II promoters are not affected. Finally, although we have been able to obtain a DNase I footprint of the fliQ promoter with CtrA we have been unsuccessful in binding CtrA to the mcpA promoter (S. E. Jones, unpublished).…”
Section: How Does Ctra Regulate Mcpap and Cagap?mentioning
confidence: 93%
“…2d and Fig. 5 (Van Way et al, 1993), fliQp (Zhuang & Shapiro, 1995), flhAp (Ramakrishnan et al, 1991 ;Sanders et al, 1992), fliXp (Mohr et al, 1998) and fliLp (Yu & Shapiro, 1992 that the mcpA promoter is different from other CtrAdependent class II promoters is provided by the finding that transcription of mcpA is inhibited when membrane synthesis is blocked (Brassinga et al, 2000), whilst other flagellar class II promoters are not affected. Finally, although we have been able to obtain a DNase I footprint of the fliQ promoter with CtrA we have been unsuccessful in binding CtrA to the mcpA promoter (S. E. Jones, unpublished).…”
Section: How Does Ctra Regulate Mcpap and Cagap?mentioning
confidence: 93%
“…The genetic origins of these proteins were unknown at the time of that study. Subsequently, the fliP and fliR genes have been characterized in several bacterial species (Carpenter et al, 1993;Mulholland et al, 1993;Malakooti et al, 1994;Hardham et al, 1995;Zhuang and Shapiro, 1995;Ge and Charon, 1997;Ohnishi et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…The unusual consensus sequence of class II promoters suggested that transcription of these genes and thus their temporal pattern of activity is controlled by a novel sigma factor [27,42,43]. However, in vitro activation of class II promoters by the Ec 73 RNA polymerase indicates that these promoters are in fact recognized by the C. crescentus housekeeping sigma factor [44].…”
Section: Control Of Early £Agellar Genes (Class Ii)mentioning
confidence: 99%
“…Initiation of £iL and £iF transcription in vitro was dependent on the presence of CtrA in the assay [44]. All CtrA-controlled promoters share a similar architecture with a CtrAbinding site (CtrA-box) overlapping the 335 region [45,46] and with nucleotides in the CtrA-box being essential for their transcriptional activity [27,42]. In vitro binding studies have shown that phosphorylation enhances the a¤nity of CtrA for the £iQ promoter approximately 50-fold [46].…”
Section: Control Of Early £Agellar Genes (Class Ii)mentioning
confidence: 99%